A multi-analytical approach for the archaeometric identification of a Roman period glass furnace in the central Nile delta. (February 2017) - Gentelli, Liesel; Medhat, AbdelRahman
Abstract: A circular structure was excavated in a suspected industrial area of ancient Thmuis (Tell Timai), and due to heavy vitrification and discolouration of the inside walls, was suspected to be a glass furnace. The excavated furnace provides a unique example to further understand the mechanisms of primary and secondary glass manufacture in Roman Egypt. Samples were subjected to a number of archaeometric investigations in order to characterise the furnace, and identify its purpose. Following attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and scanning electron microscope energy dispersive spectroscopy (SEM-EDS), we conclude that the furnace was used for glass. We propose that it is most likely that the furnace represents a small-scale, secondary glassmaking centre, shaping glass manufactured at Wadi el-Natrun, and recycling glass objects from the local area. Highlights: A secondary glass production site in the Nile delta is identified. Evidence for glass manufacture in Roman Egypt Application of analytical techniques to identify unknown samples